Threats to masculinity evoke status-quo-reinforcing racism, xenophobia, and Islamophobia - Vescio, Theresa K.; Yamaguchi-Pedroza, Katsumi; Schermerhorn, Nathaniel E. C.; Loviscky, Abigail J. (Frontiers in Social Psychology, 2025)
Culturally idealized forms of masculinity have been suggested to be endorsed and internalized by men, resulting masculine identities that are easily threatened and inspire status-quo-reinforcing outcomes. The present examined whether receiving gender-incongruent feedback, which was predicted to threaten masculinity in men (but not femininity in women), serially led to public discomfort, anger, and status-quo-reinforcing prejudice toward members of marginalized groups. To test predictions, men and women in two studies (N = 606) took an apparent gender knowledge test and received feedback indicating that their scores were more similar to the average score of women or men. Consistent with predictions, when men received gender-incongruent information they felt more public discomfort and subsequent anger that, in turn, predicted anti-Black attitudes (Study 1), anti-immigrant attitudes (Study 2), and Islamophobia (Study 2); these effects were not significant among women. The present findings replicate prior research showing that, when receiving gender-incongruent information, men experience threats to masculinity that lead to acts of dominance and aggression, which reinforce men-s dominance over women. The present findings also provide novel evidence that threats to men's masculinity—via public discomfort and anger—arouse White men's dominance over marginalized masculinities.